Incidence, Prevalence, and Trends in Endometriosis Diagnosis: A United States Population-Based Study From 2006 to 2015. Issue 11 (November 2021) - Christ, Jacob P.; Yu, Onchee; Schulze-Rath, Renate; Grafton, Jane; Hansen, Kelly; Reed, Susan D.
Abstract : (Abstracted from Am J Obstet Gynecol 2021; doi: 10.1016/j.ajog.2021.06.067). Endometriosis, defined as the presence of extrauterine endometrial tissue, often has serious symptoms that significantly impact the lives of those affected and is associated with annual health care costs of approximately $16, 500. Despite the significant societal and individual burden of endometriosis, prevalence and incidence data in the United States are lacking with prevalence rates ranging from 0.8% to 11% and incidence ranging from 4.2 to 35 per 10, 000 women-years.